2019
DOI: 10.1038/s41467-019-13092-7
|View full text |Cite
|
Sign up to set email alerts
|

Non-noble metal-nitride based electrocatalysts for high-performance alkaline seawater electrolysis

Abstract: Seawater is one of the most abundant natural resources on our planet. Electrolysis of seawater is not only a promising approach to produce clean hydrogen energy, but also of great significance to seawater desalination. The implementation of seawater electrolysis requires robust and efficient electrocatalysts that can sustain seawater splitting without chloride corrosion, especially for the anode. Here we report a three-dimensional core-shell metal-nitride catalyst consisting of NiFeN nanoparticles uniformly de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
687
1
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 986 publications
(706 citation statements)
references
References 55 publications
16
687
1
2
Order By: Relevance
“…25b) of the samples before and after the long-term stability test further confirmed the unchanged phase. Notably, when the potential increased to 1.7 V vs. RHE, at which the OER process should happen, the original peaks disappeared and the emerging broad peak at the range of 500~600 cm −1 could be assigned to the conversion of metal nitride to metal oxyhydroxide (from Co 3 N to CoOOH in our case), which has been broadly observed in previous reports regarding the OER electrocatalysis process 42,44,57,58 . Therefore, it can be concluded that the metal nitride itself could act as the active species for HzOR without observable surface change during the catalytic process.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…25b) of the samples before and after the long-term stability test further confirmed the unchanged phase. Notably, when the potential increased to 1.7 V vs. RHE, at which the OER process should happen, the original peaks disappeared and the emerging broad peak at the range of 500~600 cm −1 could be assigned to the conversion of metal nitride to metal oxyhydroxide (from Co 3 N to CoOOH in our case), which has been broadly observed in previous reports regarding the OER electrocatalysis process 42,44,57,58 . Therefore, it can be concluded that the metal nitride itself could act as the active species for HzOR without observable surface change during the catalytic process.…”
Section: Discussionsupporting
confidence: 84%
“…5a. It can be seen that a small overpotential of 41 mV is required to achieve 10 mA cm −2 for PW-Co 3 N NWA/NF, which is only 9 mV larger than that of Pt/C (32 mV) and lower than recent reported transition-metal-nitride-based HER catalysts, such as NiCoN/C nanocages (103 mV) 27 , Co-Ni 3 N (194 mV) 42 , Ni 3 N/C (64 mV) 43 and NiMoN/NF (56 mV) 44 (see details in Supplementary Table 3). The surface area is an important factor to affect the catalytic activity, we then measured the electrochemical double-layer capacitance (C dl ) of different materials to compare the electrochemical surface areas ( Supplementary Fig.…”
Section: Synthesis and Characterization Of Pw-co 3 N Nanowire Arraysmentioning
confidence: 59%
“…Dynamic evolution like this has also been found and reported. 43 In addition, the conversion of Co-phosphate to Co-oxides/ hydroxides in alkaline OER conditions has also been previously reported. 13,20,23,27,28,38,42 However, a comparison of the published works on OER performance of Co-phosphate and Cooxides/hydroxides reveals no large differences in OER overpotential among them.…”
Section: Electrochemical Properties Of Au@co 2 P Npsmentioning
confidence: 85%
“…In addition, compared to the emerging seawater oxidation, UOR can avoid chlorine gas generation because of the lower reaction potential of UOR than that for chlorine evolution reaction (E 0 = 1.36 V vs RHE). 8 Therefore, using UOR to replace OER can not only save the energy input but also reduce the contamination of urea-rich wastewater. 4,6 Compared to OER, UOR suffers from even more sluggish kinetics because of the complicated 6etransfer process, which needs high performance catalysts to decrease the overpotential to achieve an e cient device.…”
Section: Introductionmentioning
confidence: 99%